Novel applications of plant tissue culture and conventional breeding techniques to space biology research - Krikorian, Abraham D.; Justus Liebig University Giessen (My University, 2001)
In the minds of many, plant cell and tissue culture may now be viewed as a well-developed technology. It has been all but reduced to a tool to solve practical problems and contribute to plant improvement. While this is so in some instances, it is definitely not so in trying to utilize and integrate plant cell and tissue culture into the projected needs of Space biology programs. This is not merely because of the challenges posed by the unusual physical environment of Space such as microgravity, or the constraints posed by Spaceflight protocols but is due to our inadequate knowledge of the factors that control plant growth and development, including systems as they grow in vitro. The premature (and in many cases unrealistically optimistic) initial assessments of what is really known about what happens in aseptic culture belies the many fundamental developmental and physiological questions that still need to be answered before plant
Keywords: ddc:570